Designing lesson studies to support teachers’ professional development - Ponte, João Pedro da (2018)
In this paper we address design issues of lesson studies that aim to support practicing teachers’ professional development. We discuss these issues based in the cases of two lesson studies that we conducted in the academic year of 2013-2014 in a cluster of schools in Lisbon. We strive to show that, besides the consideration of the mathematical content, task features, and focus on student reasoning, attention needs to be paid to organizational issues regarding the way the teachers are invited to become involved in lesson studies and to the collaborative environment provided. We also conclude critical design factors for the success of a lesson study include the investigation style of the whole activity, the combination of teachers’ experiential knowledge with research knowledge, and the exploratory and collaborative environment that frames the activities that the teachers undertake.